Analysis of access to dental services through the first dental programmatic appointment indicator in Pernambuco: a comparative study between the years 2001 and 2009 - Italene Barros Viana; Petrônio José de Lima Martelli; Fernando Castim Pimentel (Universidade de Fortaleza, 2012)
Objectives: To analyze access to individual dental care developed in the state of Pernambuco, comparing years 2001 and 2009, related to Oral Health Teams in Family Health Strategy. As well, to verify the existence of any inequities in access to dental care, according to geographical region and administrative region. Methods: This descriptive ecological temporal-trend study was performed using secondary data sources, from health care information systems on a national basis. The first dental programmatic appointment was used as the primary care indicator for evaluation of assess to individual dental care. Results: Data analysis showed a significant increase in the number of oral health teams in the state, over the studied years (from 132 teams in 2001 to 1,296 in 2009), representing an increase of 881.82%. Regarding the first dental appointment, an enhancing in coverage was observed (from 10.04% in 2001 to 16.87% in 2009). Conclusions: Despite the positive growth in the first dental appointment indicator, utilization and access to dental services on a programmatic way in primary care still remain low. Numbers indicate relatively low access rates, and reveal that reality of services is far distant from what is constitutionally guaranteed. These results point to the need of rethinking the practice and work to build a system mainly focused on coverage enlargement and on the needs of communities.